The Impact of Health Education Based on Theory of Planned Behavior on the Prevention of AIDS among Adolescents - Pakpour Hajiagha A; Mohammadi Zeidi I; Mohammadi Zeidi B (Iran University of Medical Sciences, 2012)
Background & aims : Adolescents are among the most vulnerable age groups against AIDS and other sexually transmitted diseases . The aim of this study was to assess the impact of health education based on Theory of Planned Behavior on the prevention of AIDS among high school students in Qazvin city.   Material & Methods : It was a quasi experimental study that was conducted on 120 students in boys' high schools in Qazvin. The students were randomly assigned into either control or experimental groups (each 60). Data was gathered before and after educational program. The instruments included questions related to demographic characteristics, a questionnaire for assessing constructs of theory of planned behavior and an observation checklist to assess refusal skills and stalling risk suggestions . Educational intervention was conducted in 5 focus group discussions each lasting for 45-60 minutes with emphasis on the above mentioned theory. An educational pamphlet also was given to the subjects. Data were collected before and 3 months after training and was analyzed by Mann-Whitney U test, Wilcoxan test, paired t test, Chi-square and ANOVA using SPSS-PC (v. 17.0).   Results : The average age of the subjects was 16± 3.29 years. No difference was detected between demographic characteristics of the control and experimental groups. There was also no difference between the groups regarding cognitive variables (knowledge, attitude, perceived behavior control and intention) before the intervention. The adolescents in the experimental group reported higher scores for the cognitive variables compared with the control group (P=0.001). The results related to refusal skills and stalling risk suggestions indicated that the educational intervention increased these skills at the end of study (P<0.05).   Conclusion : The findings revealed that an educational intervention based on the theory of planned behavior results in the formation of refusal skills and stalling risk suggestions related to HIV/AIDS behaviors among male adolescents.  Received: 27 Aug 2012   Accepted: 10 Nov 2012